Implementation of Disciplinary Character Education at the Integrated Islamic Kindergarten Imam Syafi’i and Integrated Islamic Kindergarten Bintang Qur'ani, Banjarmasin City - Noorainah, Noorainah; Darmiyati, Darmiyati; Sakerani, Sakerani (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to describe and analyze the management of character education learning discipline in Kindergarten. The results of the study show: 1). The implementation of Character Education is adjusted based on each curriculum; 2). The role of the Teacher is to prepare a teaching implementation plan, conduct learning and then carry out learning evaluations, 3). Obstacles in the Implementation of Character Education Discipline, namely: a). Motivation and support from parents, b). The need for direct practice by teachers when at school and repetition from parents, c). Involvement of everyone at home; 4). Evaluation in the implementation of education in three time periods: daily evaluation, monthly evaluation and semester evaluation.